Making Climate Smart Agriculture Innovations One Health Sensitive - Osae, Michael; Dzepe, Daniel; Clottey, Victor; Yeboah, Stephen; Dalaa, Mustapha Alasan; Tahidu, Osman; Tepa-Yotto, Ghislain; Agboton, Cyriaque; Tamo, Manuele (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
That is, the CSA practices ensure a healthy ecosystem (humans, animals and plants, and their shared environment). This policy brief highlights CSA and One Health concepts and outlines how CSA innovations and for that matter, any innovation can be made One Health sensitive. Ensuring CSAs are One Health sensitive brings great benefit to our agri-food systems, livelihoods as well as to the ecosystem.